2020
DOI: 10.1155/2020/8814878
|View full text |Cite
|
Sign up to set email alerts
|

Modulated Electrohyperthermia: A New Hope for Cancer Patients

Abstract: According to the World Health Organization, the prevalence of cancer has increased worldwide. Oncological hyperthermia is a group of methods that overheat the malignant tissues locally or systematically. Nevertheless, hyperthermia is not widely accepted, primarily because of the lack of selectivity for cancer cells and because the temperature-triggered higher blood flow increases the nutrient supply to the tumor, raising the risk of metastases. These problems with classical hyperthermia led to the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 102 publications
1
8
0
Order By: Relevance
“…Improvements were reported also in tumor response for locally advanced pancreatic carcinoma a consequence of the association of CHT to mEHT with a DCR of 95% that were in agreement with previous data: DCR of 71%-96%[ 8 - 11 ] and resulted higher than that reported by CHT associated with local hyperthermia, showing a DCR of 50%-61%[ 17 - 19 ]. The level of hyperthermia related toxicity was 5% as reported by other studies, showing G2 pain and a skin rash and 5% grade III–IV toxicity[ 15 , 18 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Improvements were reported also in tumor response for locally advanced pancreatic carcinoma a consequence of the association of CHT to mEHT with a DCR of 95% that were in agreement with previous data: DCR of 71%-96%[ 8 - 11 ] and resulted higher than that reported by CHT associated with local hyperthermia, showing a DCR of 50%-61%[ 17 - 19 ]. The level of hyperthermia related toxicity was 5% as reported by other studies, showing G2 pain and a skin rash and 5% grade III–IV toxicity[ 15 , 18 ].…”
Section: Discussionsupporting
confidence: 90%
“…Hyperthermia has been used as cancer therapy for decades, especially for its benefits in enhancing chemotherapy and radiotherapy efficacy[ 6 , 14 - 22 ]. mEHT has been more recently introduced among hyperthermia methods, targeting malignant cell membranes and the extracellular matrix and overcoming the issue of homogenous tissue heating[ 7 , 8 ]. The efficacy of mEHT was shown for several types of tumors, including pancreatic cancer, increasing tumor response and survival[ 5 , 9 , 15 - 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An extrinsic effect (abscopal) is a process in which local tumour treatment leads to the antitumour impacts observed outside the radiation field at a considerable distance from it [76]. Based on the existing literature, abscopal effects are observed in patients treated with RT [77], oncothermia [78] or a combination of them. Local irradiation of a tumour at one site induces the entry of tumour antigens or inflammatory response factors into the circulatory system, which may cause an increased defence response directed against non-irradiated tumour lesions displaying similar tumour antigens [79].This is supported by the potential benefits of immunotherapy and the evidence of the activity of immune checkpoint inhibitors in mCRPC [80], [81].…”
Section: P R E P R I N Tmentioning
confidence: 99%
“…The functional and bioelectric features of the malignant cells drive the selective process, which, together with the dynamic interactions and thermal exchanges, kills the cancer cells in an apoptotic way. Without going into details, mEHT exploits the biophysical differences of cancer cells that their energy absorption on the membrane rafts is different than those of healthy host cells, furthermore, damage-associated molecular patterns (DAMPS) will occur and all of these eventually lead to programmed or immunogenic tumor cell death [ 25 , 26 ]. The mEHT method re-sensitizes the refractory cases, can act as monotherapy as preclinical results and case studies suggested [ 25 , 27 , 28 , 29 ], and increases the survival time and QoL in parallel.…”
Section: Introductionmentioning
confidence: 99%